The Rhetoric of Football Fans: Theoretical Foundation and a Practical Example - Abdel Latif, IMAD (El Omda in Linguistics and Discourse Analysis, 2019)
Abstract: The goal of this article is to study the discourses of football fans from rhetorical perspectives. It discusses their theoretical foundations and gives a particular attention to the Rhetoric of Audience’s approach. The article highlights the relevant subjects that could be tackled within this approach, the analytical frameworks that could be employed, and research questions that could be addressed. To illustrate how the Rhetoric of Audiences approach the football discourses, I analyze a Moroccan chant entitled (Fi Bladi Zalmoni In my home, they aggrieved me). It is one of the most popular chants in the Arab world in 2018. In particular, I will investigate how this chant represents a kind of rhetorical responses by analyzing its dialogicality moves and personal pronouns.